Tapes of water hexamer clusters in the interlayer space of a 2D MOF: Structural, spectroscopic and computational insight of the confined water - Bernini, Maria Celeste (2012)
The synthesis, crystal structure and characterization of [Er2(C4H4O4)3(H2O)4]. 6H2O, with particular emphasis on the structural details and the vibrational behavior of the highly organized sub-net of waterare reported. X-ray structural analysis reveals that the hybrid framework, which can be classified as belonging to the I0O2 type, acts as a host of an infinite tape of six-membered water rings with distorted chair conformation. The water network extends between the hybrid layers helping the close packing and the stabilization of the structure through H-bond interactions, with further development of the supramolecular tridimensional structure. The self-assembly of the hydration water molecules is conditioned by the hybrid host, forcing them to adopt a less stable conformation when compared with hexagonal ice. The vibrational spectra of partially and completely dehydrated samples as well as of partially isotopic diluted ones have been obtained and analyzed. In order to guide the assignment of the vibrational spectra a theoretical calculation was performed at the B3LYP/6-31G**  level for a model consisting of three water clusters.